Sensitivity Analysis and Optimal Funding Strategy for Catering MSMEs in Facing Raw Material Price Fluctuations to Increase Profitability - Limbong, Priscila O.G.; Febrisutisyanto, Ady (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2026)
Micro, Small, and Medium Enterprises (MSMEs), particularly in the catering sector, often experience fluctuations in raw material prices, which directly affect their cost structures and profitability. This condition poses a challenge for MSMEs in optimizing financing to maintain financial stability and business continuity. For this reason, innovation is needed in the form of sensitivity analysis and optimal funding source analysis to overcome the challenges MSMEs face. Aim: To analyze the impact of raw material price fluctuations on MSME profitability and to determine the optimal financing structure through sensitivity analysis and evaluation of funding sources. Method: Sensitivity analysis was conducted using raw material price data from 2020 to 2023 to assess changes in net profit. Gross profit and net profit were calculated based on sales revenue, cost of goods sold, and operating costs. The optimal financing source was assessed by calculating the Weighted Average Cost of Capital (WACC) and evaluating profitability using the Net Present Value (NPV) and the Internal Rate of Return (IRR). The results indicate the attainment of a break-even point where total revenue equals total costs, providing a basis for MSMEs to formulate appropriate pricing strategies to achieve profitability.